2012
DOI: 10.1148/radiol.12111303
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation as a Substitute for Surgery in Elderly Patients with Nonresected Breast Cancer: Pilot Study with Long-term Outcomes

Abstract: RF ablation in elderly patients with nonresected breast cancer is well tolerated and efficient at 1-year follow-up. The technique is not recommended for lobular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…Similarly to previous studies [16,17,26], MR imaging clearly demonstrated the ablation area without enhancement in all patients, and it correlated well with histological finding. Moreover, the margin of the ablation zone was clear and smooth in all cases.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly to previous studies [16,17,26], MR imaging clearly demonstrated the ablation area without enhancement in all patients, and it correlated well with histological finding. Moreover, the margin of the ablation zone was clear and smooth in all cases.…”
Section: Discussionsupporting
confidence: 86%
“…Since satisfied cosmetic outcomes may be obtained by nonsurgical ablative therapies without the removal of breast tissue, ablative therapies have been evaluated in many clinical research studies [3,[15][16][17][18]. Our previous phase I ablation-resection study firstly shows that MWA of small breast cancers is feasible under general anesthesia, but the extent of ablation zone may be underestimated [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques have been used to ablate cavity margins after standard surgical excision, [96][97][98][99] as well as to ablate the primary cancer itself. [100][101][102] Owing to the percutaneous instrumental manipulation involved, these techniques can have similar complications to standard surgery, including scarring, skin burns, haematomas, and infection. 96,100,101 The percutaneous techniques for the treatment of breast cancer all apply the same principles of placement of treatment probes into the centre of the lesion under ultrasound-guidance.…”
Section: Minimally Invasive Percutaneous Surgerymentioning
confidence: 99%
“…As ablation makes the posterior evaluation of molecular markers impossible, these markers must be determined from a previous biopsy (43). Radiofrequency ablation is not recommended in invasive lobular carcinoma due to this cancer's higher risk of microscopic spread (44).…”
Section: Radiofrequency Ablation In Early Breast Cancermentioning
confidence: 99%